2012
DOI: 10.4047/jap.2012.4.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber reinforcement on impact strength of heat polymerized polymethyl methacrylate denture base resin:in vitrostudy and SEM analysis

Abstract: PURPOSEThe aim of this in-vitro investigation was to describe the effect of reinforcement with different fibers on impact strength of heat polymerized polymethyl methacrylate (PMMA) denture base resin and to analyze the effect of surface treatment of the fibers on the impact strength.MATERIALS AND METHODSThe specimens were fabricated from the dies formed as per standard ASTM D4812. 2% by weight of glass, polyethylene and polypropylene fibers were incorporated in the PMMA resin. The Izod impact testing was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
54
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 22 publications
2
54
0
3
Order By: Relevance
“…19,20 A study by Johnston et al showed that 68% of acrylic resin denture manufacture broke in a few years mainly because of impact strength. 21 The weakness of transversal strength happen because of denture base tense while mastication which trigger crack. 11,16,17,20 Effect Of Thermocycling And Polyethylene Fibre Addition On Impact And ….…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 A study by Johnston et al showed that 68% of acrylic resin denture manufacture broke in a few years mainly because of impact strength. 21 The weakness of transversal strength happen because of denture base tense while mastication which trigger crack. 11,16,17,20 Effect Of Thermocycling And Polyethylene Fibre Addition On Impact And ….…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] A few fibre types reported can increase mechanical properties such as glass, polyethylene, silica, polycarbonate, carbon (graphite), sapphire, ceramic, nylon, and aramyde (polyamides polyaromatic). 8,9,11,20,21 The most commonly used fibre as acrylic resin denture base reinforcing material is polyethylene fibre. Polyethlylene fibre has several profitable properties such as easy to manipulate, biocompatible, natural colours, bond well with resin matrix and good aesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanical properties of heat-polymerized polymethyl methacrylate is its impact strength [1]. The fractures of acrylic resin denture base after several years of usage were 68% due to its impact strength [3].…”
mentioning
confidence: 99%
“…9,10 Ayrıca farklı sektörlerde asfalt ve beton karışımlarının içlerine katılarak mekanik özelliklerini geliştirmede de kullanılmaktadır.…”
unclassified
“…9,10 Çalışmamızın amacı ısı ile polimerize olan kaide materyalini kuvvetlendirmek için farklı oranlarda ilave edilen polipropilen fiberin akriliğin transvers direnç ve yüzey pürüzlülüğü üzerine etkisini araştırmaktır. Çalışmamızda, polipropilen ilaveli ısı ile polimerize olan PMMA rezinin transvers direnci ve yüzey pürüzlülüğü değerleri arttıracağı hipotezi test edilmektedir.…”
unclassified